The Effects of Zinc Supplementation on Growth, Diarrhea, Antioxidant Capacity, and Immune Function in Holstein Dairy Calves - Junhao Liu; Fengtao Ma; Allan Degen; Peng Sun (Animals, 2023)
The current study examined the effects of supplementary zinc proteinate (ZnPro) and zinc oxide (ZnO) on growth performance, diarrhea, antioxidant capacity, immune function, and mineral element concentrations of calves aged 1 to 28 days. A total of twenty-four newborn calves were divided randomly into 3 groups (n = 8; 2 males and 6 females per group), and each received: 0 mg/d Zn (CON), 627 mg/d ZnPro (80 mg/d Zn; ZnPro group), and 101 mg/d ZnO (80 mg/d Zn; ZnO group). The calves received the additive in their milk during the first 28 days of life. Compared with the CON group: ZnPro and ZnO improved average daily gain (ADG) and decreased the feed:gain ratio (FGR) between days 1 and 14 (p < 0.05), while the ADG increased and FGR decreased only in the ZnPro group between days 1 and 28 (p < 0.05). The incidence of diarrhea decreased (p < 0.05) in the ZnPro and ZnO groups between days 15 and 28 as well as days 1 and 28, but decreased (p < 0.05) only in the ZnPro group between days 1 and 14. The serum immunoglobulin G (IgG) concentration of the ZnPro and ZnO groups increased on days 14 and 28 (p < 0.05). ZnPro supplementation increased serum IgM concentration during the whole study, while ZnO enhanced serum IgM concentration only on day 14 (p < 0.05). In the ZnO group, the serum concentration of cytokines interleukin (IL)-10 increased on day 14, while that of IL-1β increased on day 28 (p < 0.05). In addition, ZnPro reduced the serum malondialdehyde (MDA) concentration on days 14 and 28 (p < 0.05). Both ZnPro and ZnO increased the serum concentrations of alkaline phosphatase (ALP) and metallothionein (MT) on day 14 (p < 0.05). With zinc supplementation, plasma Zn concentration increased (p < 0.05) on days 14 and 28 of age. We concluded that supplementary ZnPro and ZnO reduced incidences of diarrhea and promoted the immune function, but ZnPro improved the growth performance and antioxidant capacity of Holstein dairy calves to a greater extent.